Assessing the value of public investment into biological control research for invasive alien plants : the ARC PPRI Weeds Research Division - Scarr, Lowell Martin (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2016)
This study investigates the economic impact of the ARC PPRI Weeds Research Division. The Division researches appropriate methods of biological control for invasive alien plants (IAPs). These plants pose an increasing threat to environmental integrity and ecosystem service provision impacting on economic potential. Since the work of the Division is considered a public good, a predominantly descriptive approach has been adopted for the valuation process. A combination of quantitative cost analysis and a qualitative study of the impacts of research and invasive alien plants is used to deal with the challenges associated with non-market valuation. The study found that investment into the Weeds Division is a valuable activity that supports the long-term growth potential of the South African economy. The role of a well-functioning environment is highlighted as an essential base for the creation of sustained growth opportunities in any society. It was determined that investment into the Division should be increased into the future to support efficient spending of scarce state funds. Biological control research was found to provide strategic future growth potential, creating opportunities for the development of a competitive advantage in the biotechnology and environmental management sectors. The study adds to the increasing move towards a more holistic view of economic valuation, taking factors other than pure finance and econometrics into consideration. This is an important shift in prevailing economic thought, as a realisation is reached that a single, or even triple, bottom line is an outdated and insufficient decision making basis.
Keywords: Alien plants -- Biological control; Invasive plants -- Biological control; Alien plants -- Economic aspects; Invasive plants -- Economic aspects; Weeds -- Biological control